Development of Two-Photon Photosensitizers and Its Application in Photodynamic Therapy to Cancer Models - 이동준 (The Graduate School, Ajou University, 2024)
최근 다양한 방법을 이용하여 질병 또는 암을 진단하고 치료하고 있다. 그 중 광역학 치료(PDT)는 빛을 이용하여 암의 성장을 억제하거나 세포 데미지를 가하는 치료 기술이다. 광역학 치료는 원하는 부위만 선택적으로 치료가 가능하며, 부작용이 적고 시술시 고통이나 통증이 없다는 장점이 있다. 광역학 치료는 빛, 산소, 광감각제라는 3가지 중요한 요소를 고려해야된다. 먼저 광역학 치료에서는 LED 빛을 많이 사용한다. 그런데 단파장을 사용하는 LED는 높은 에너지로 인한 세포에 손상을 입힌다. 또한 낮은 투과력이라는 단점이 있다. 그렇기 때문에 장파장 영역에 빛에 활성을 보이는 광감각제 개발은 필수적이다. 그 중 근적외선 영역의 이광자 레이저는 LED 빛의 단점을 보완하는 기술로 주목을 받고 있다. 이광자 레이저는 낮은 에너지를 갖는 두 개의 광원을 사용하여 생체 시료에 적은 손상을 가한다. 또한 근적외선 영역을 사용하기 때문에 조직 깊은 곳까지 빛이 투과할 수 있는 장점을 가지고 있다. 최근에 광역학 치료 분야에서 이광자 광감각제의 개발과 생체 시료에 대한 응용 연구가 많이 진행되고 있다._x000D_ 이광자 광감각제를 만들기 위해 이광자 흡수 효율이 좋은 형광 염료를 고안하였다. 장파장 영역에서 많이 사용되는 형광단은 cyanine 유도체이다. 이들은 링이 open된 구조를 가지고 있다. open 형태의 cyanine 유도체들은 낮은 광안정성과 높은 photobleaching이라는 단점을 가지고 있다. 이러한 문제를 극복하기 위해 폐쇄형 시아닌 유도체 합성 전략이 고안되었다. 합성된 cyclo cyanine (CC) 염료는 이광자 흡수(TPA) 및 형광 양자 수율이 좋았다. 또한 높은 photostability와 낮은 photobleaching를 보였다. CC 염료는 이전의 cyanine 염료의 문제들을 보완하였다. 이광자 형광 염료인 CC 염료에 azo bridge 포함한 이광자 광감각제(ACC)를 만들었다. azo bridge는 빛을 받게 되면 일부는 amine으로 끊어지게된다. 하지만 일부는 산소와 만나 세포손상을 일으키는 자유라디칼을 만들게 된다. 그리고 암 선택성을 높이기 위해 biotin group을 연결하였다. biotin은 비타민의 일종으로 암이 성장하는데 필요한 영양분이다. azo가 포함된 ACC와 암 타겟 그룹 biotin이 연결된 ACC-B를 합성하였다. ACC-B는 이광자 레이저에 의해 높은 활성 산소종(ROS) 생산 효율을 보였다. 뿐만 아니라 ACC-B는 대장암 조직에 선택적으로 uptake 되었다. 그리고 이광자 레이저를 조사하였을 때 조직 깊은 곳까지 ROS가 발생하였다. 치료 할 수 있는 연구를 진행하였다. 이러한 이광자 감광제는 광역학 치료 분야의 발전에 크게 기여할 것으로 기대된다._x000D_ ROS를 효과적으로 발생시키기 위해서는 단일항 상태(singlet state)에서 삼중항 상태(triplet state)로의 계간 교차(intersystem crossing, ISC)가 잘 일어나야 된다. heavy atom은 단일항과 삼중항 상태 사이의 스핀-궤도 결합(SOC)을 향상시켜 ISC 효율을 높입니다. 따라서 분자 내에 heavy atom을 포함하는 것은 ISC 효율이 증가하고 그로 인해 ROS가 잘 발생하도록 도움을 준다. 이러한 전략을 이용하여 이전에 개발한 이광자 형광 염료에 heavy atom을 포함하는 합성법을 고안하였다. 진단용 이광자 형광 염료로 사용되던 BN, BO, BS는 N, O, S atom이 포함되어있다. 이 염료에 heavy atom인 Se, Te atom으로 대체하였다. Se, Te을 포함한 이광자 광감각제(BSe, BTe)는 훌륭한 ROS 발생 효율을 확인하였다. 또한 BSe에 암 타겟 unit을 연결한 BSe-B를 합성하였다. BSe-B를 3D-spheroid 종양모델과 대장암 조직에서 연구를 진행하였고 정상모델과 암 모델을 훌륭하게 구분하였다. 또한 이광자 레이저를 조사하였을 때 생체 시료 깊은 곳까지 치료할 수 있는 가능성을 보였다. 이를 통해 이광자 광감각제는 다양한 질병 및 암을 치료할 수 있는 훌륭한 도구중 하나로써 가능성을 입증하였다. 그리고 의료분야에 유용하게 사용될 수 있음을 기대할 수 있다.|Recently, various methods are being used to diagnose and treat diseases or cancer. Among them, Photodynamic Therapy (PDT) is a treatment technique that uses light to suppress cancer growth or induce cellular damage. PDT has the advantage of being able to selectively treat specific desired areas, minimizing side effects and causing no pain or discomfort during the procedure. Photodynamic therapy must consider three important factors: light, oxygen, and photosensitizer. First, LED light is widely used in photodynamic therapy. However, LED that use short wavelengths have the disadvantages of causing cell damage due to their high energy and having low penetration. Therefore, it is essential to develop photosensitizers that are active in the long-wavelength range. Among them, two- photon lasers in the near-infrared range have gained attention as a technology to complement the limitations of LED light. Two-Photon (TP) lasers cause little damage to biological samples by using two light sources with low energy. Additionally, because it uses the near-infrared region, it has the advantage of allowing light to penetrate deep into the tissue. Recently, in the field of photodynamic therapy, much research has been conducted on the development of TP photosensitizers and their application to biological samples. To create a TP photosensitizer, a fluorescent dye with good two-photon absorption (TPA) efficiency was designed. The fluorophore widely used in the long wavelength range is a cyanine derivative. They have an open ring structure. Open form cyanine derivatives have the disadvantages of low photostability and high photobleaching. To overcome these problems, a strategy for synthesizing closed-type cyanine derivatives was designed. The synthesized cyclo cyanine (CC) dye had good TPA and fluorescence quantum yield. It also showed high photostability and low photobleaching. CC dye compensated for the problems of previous cyanine dyes. We created a TP photosensitizer (ACC) containing an azo bridge in CC dye, a TP fluorescent dye. When an azo bridge is exposed to light, some of it is broken into amines. However, some of it meets oxygen and creates free radicals that cause cell damage. And a biotin group was connected to increase cancer selectivity. Biotin is a type of vitamin and a nutrient necessary for cancer growth. ACC-B was synthesized by linking azo- containing ACC with the cancer target group biotin. ACC-B showed high reactive oxygen species (ROS) production efficiency by TP laser. In addition, ACC-B was selectively uptake in colon cancer tissues. And when irradiated with a TP laser, ROS was generated deep into the tissue. Research into possible treatments was conducted. It is expected that these TP photosensitizers will greatly contribute to the advancement of the field of photodynamic therapy. In order to effectively generate ROS, intersystem crossing (ISC) from the singlet state to the triplet state must occur well. Heavy atoms enhance the spin-orbit coupling (SOC) between singlet and triplet states, increasing ISC efficiency. Therefore, including a heavy atom in the molecule increases ISC efficiency and thus helps generate ROS. Using this strategy, we designed a synthesis method that included a heavy atom in a previously developed TP fluorescent dye. BN, BO, and BS, which were used as TP fluorescent dyes for diagnosis, contain N, O, and S atoms. This dye was replaced with heavy atoms Se and Te atoms. TP photosensitizers (BSe, BTe) containing Se and Te were confirmed to have excellent ROS generation efficiency. Additionally, BSe-B was synthesized in which a cancer target unit was linked to BSe. BSe-B was studied in a 3D-spheroid tumor model and colon cancer tissue, and excellent distinction was made between normal and cancer models. In addition, when irradiated with a TP laser, it showed the possibility of treating deep areas of biological samples. Through this, the TP photosensitizer has proven its potential as an excellent tool for treating various diseases and cancer. And it can be expected that it can be usefully used in the medical field.
학위논문(박사)--에너지시스템학과,2024. 2
Keywords: Colon caner tissue; Photodynamic Therapy; Photosensitizer; Small molecule; Two-Photon